نظرية الحقول الدِلالية واستخدامها في بناء الوحدات الدراسية لتدريس اللغة العربية للدارسين التايلانديِين : دراسة وصفية وتحليلية - وسترات، وليلاك (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study aims to investigate a new approach in teaching Arabic language to Thai learners at the intermediate level. To achieve this objective, a descriptive-analytic method was adopted to discuss the related issues in teaching and learning vocabulary, with a focus on Semantic fields and its approaches in teaching vocabulary. The most common useful Arabic words outlined by Rushdy T. were chosen as the essential data of this study. Then, this research distributed a questionnaire in order to filter the mentioned list. This was done in order to get the opinions of the targeted students about the difficulty level of Rushdy's word list. The result of this was that 258 out of 1000 words are considered as the most difficult on the list. Based on this result, this study designed 20 lessons using the unit method in lesson design combined with the approaches of the Semantic field in vocabulary teaching. Finally, it is found in this study that the use of the Semantic field approach in teaching vocabulary has a great impact on vocabulary acquisition in the Arabic language. Therefore, this study recommends that further research should focus on collecting a special list of commonly used words in Thai society. This list should be translated in the Arabic language and adopted in the teaching of the Arabic language and vocabulary in Thailand.